Lokalizatsiia genov ecs, dor i swl u vos'mi vidov drozofil. [Localization of ecs, dor and swl genes in eight Drosophila species.] - Kokoza, E.B.; Belyaeva, E.S.; Zhimulev, E.F. (Genetika, 1991)
The DNA sequences from Drosophila melanogaster early ecdysterone-inducible puff 2B have been located in 8 Drosophila species by in situ hybridization. The location site of the ecs, dor and swi genes in D. funebris, D. virilis, D. hydei, D. repleta, D. mercatorum, D. paranaensis is a puff on the telomeric and of X chromosome; in D. kanekoi it is the puff in distal part of X chromosome; and in D. pseudoobscura it is the puff in proximal portion of X chromosome. So, conservative organization of DNA sequences located in D. melanogaster 2B puff could be suggested. Dispersed distribution of some DNA segments from the region studied in D. hydei chromosomes was revealed.